Raman spectroscopic characteristics of diallyl trisulfide acting on trans‐crotonaldehyde. (14th July 2015) - Su, Yanbin; Chen, Lei; Cheng, Yingkun; Zhang, Fengrong; Su, Yanwen; Li, Zhengqiang
Abstract : In this paper, the molecular mechanism of diallyl trisulfide (DATS) on trans‐crotonaldehyde (TCA) was studied by UV–vis absorption and Raman spectroscopies combining with density functional theory calculations. Experimental results indicate that the introduction of DATS can not only make the maximum absorption peak of TCA shift 15 nm, but also obviously alter the Raman vibrational frequency of aldehyde (―CHO). In addition, the Raman intensity of TCA decreased significantly, especially in the presence of mitochondria. Our theoretical calculations reproduce fairly well the experimental data. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, the molecular mechanism of diallyl trisulfide (DATS) on trans‐crotonaldehyde (TCA) was studied by UV–vis absorption and Raman spectroscopies associated with density functional theory calculations. Experimental results indicate that the introduction of DATS can not only make the maximum absorption peak of TCA shift 15 nm, but also obviously alter the Raman vibrational frequency of aldehyde (―CHO). In addition, the Raman intensity of TCA decreased significantly, especially in the presence of mitochondria. Our theoretical calculations reproduce fairly well the experimental data.